Relaxation mechanism of GaP grown on 001 Si substrates: influence of defects on the growth of AlGaP layers on GaP/Si templates. Issue 20 (18th October 2021) - Pantzas, K.; Beaudoin, G.; Bailly, M.; Martin, A.; Grisard, A.; Dolfi, D.; Mauguin, O.; Largeau, L.; Sagnes, I.; Patriarche, G.
ABSTRACT: The mechanical stability of commercial GaP/Si templates during thermal annealing and subsequent growth of GaP and AlGaP using metal-organic chemical-vapour deposition is investigated. Although the as-grown GaP layer of the template originally presents an excellent surface morphology, annealing at temperatures between 645 ∘ C to 845 ∘ C to remove the native oxide prior to growth leads to plastic relaxation, accompanied by a variety of defects, including a dense grid of micro-twins. These micro-twins detrimentally affect GaP and AlGaP layers grown subsequently on the template.